A student's guide to the mathematics of astronomy - Fleisch, Daniel A.; Kregenow, Julia (Cambridge : Cambridge University Press, 2013)
The study of astronomy offers an unlimited opportunity for us to gain a deeper understanding of our planet, the Solar System, the Milky Way Galaxy and the known Universe. Using the plain-language approach that has proven highly popular in Fleisch's other Student's Guides, this book is ideal for non-science majors taking introductory astronomy courses. The authors address topics that students find most troublesome, on subjects ranging from stars and light to gravity and black holes. Dozens of fully worked examples and over 150 exercises and homework problems help readers get to grips with the concepts in each chapter. An accompanying website features a host of supporting materials, including interactive solutions for every exercise and problem in the text and a series of video podcasts in which the authors explain the important concepts of every section of the book.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Astronomy -- Mathematics -- Textbooks